Assessment of Genetic Diversity among Wild Ruta chalepensis L. from the North of Jordan - Zakaria Al-Ajlouni; Osama Migdadi; Ibrahim Makhadmeh; Abdallah Aldahadha; Shireen Hasan; Ayed M. Al-Abdallat (Diversity, 2022)
Ruta chalepensis, known as Fringed Rue, is a small shrub of the Rutaceae family. To date, there is no record of its natural distribution across Jordan, a country located in the eastern part of the Mediterranean basin, and there are no previous studies on its genetic diversity in the region. Therefore, this study was conducted to assess the genetic diversity of R. chalepensis in the northern parts of Jordan using morphological trait and amplified fragment length polymorphism (AFLP) analyses. For the morphological traits, the analysis of variance indicated that there were significant differences between the identified populations. The Shannon diversity indices showed relatively high values, indicating the existence of a high variability among the identified populations. The principal component analysis explained 82% of the variation between the collected plants, and a clear separation of the collected individuals from the Jarash-A, Jarash-B and Ajloun-B populations from the rest of the populations was observed. The heatmap clustering was in general agreement with the results of the principal component analysis, with the plant height, rachis length and plant width considered as the discriminative traits. The AFLP analysis using eight different primer combinations generated 59 polymorphic bands, with an average polymorphism information content value of 0.32. The phylogenetic analysis identified three main clusters, with the first cluster including 65% of the individuals collected from the Jarash and Ajloun provinces, with a clear separation of the Jarash-B population. The AMOVA revealed that the genetic variation between the populations contributed 30% of the total genetic variation, while the variation within the populations explained 70%. In conclusion, morphological traits and molecular markers were used successfully to assess the genetic diversity among wild R. chalepensis from the north of Jordan, and such data can be used for future conservation plans and utilization purposes.